Local order around tungsten atoms in tungstate fluorophosphate glasses by X-ray absorption spectroscopy - Poirier, G. L.; Cassanjes, F. C.; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Michalowicz, A.; Poulain, M. (Elsevier B.V., 2005)
X-ray absorption spectroscopy was used to study the local environment of tungsten atoms in NaPO3-BaF2,-WO3 glasses and the results were compared with crystalline references Na2WO4 and WO3. XANES measurements at the W-L-1 edge allowed to determine a distorted octahedral environment of tungsten atoms in these glasses similar to the local order of tungsten in monoclinic WO3. Extended X-ray absorption fine structure (EXAFS) has been used as a local probe to monitor the effect of WO3 concentration on the tungsten environment. Based on an analysis of the EXAFS data, we proposed a three-shell model of oxygen atoms around tungsten as in monoclinic WO3. With increasing WO3 concentration, it was found that R-2 decreases from 1.96 to 1.92 angstrom whereas R-3 increases from 2.07 to 2.12 angstrom. (c) 2005 Elsevier B.V. All rights reserved.